2016
DOI: 10.1016/j.ajhg.2016.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Rare Inherited and De Novo CNVs Reveal Complex Contributions to ASD Risk in Multiplex Families

Abstract: Rare mutations, including copy-number variants (CNVs), contribute significantly to autism spectrum disorder (ASD) risk. Although their importance has been established in families with only one affected child (simplex families), the contribution of both de novo and inherited CNVs to ASD in families with multiple affected individuals (multiplex families) is less well understood. We analyzed 1,532 families from the Autism Genetic Resource Exchange (AGRE) to assess the impact of de novo and rare CNVs on ASD risk i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
145
2
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(164 citation statements)
references
References 78 publications
15
145
2
2
Order By: Relevance
“…Of note, the ascertainment strategies used in both TD cohorts did not restrict to apparently simplex families, as was done in the SSC. Given the evidence for an increased burden of de novo variation in simplex versus multiplex families in ASD (e.g., Leppa et al, 2016), it would be reasonable to hypothesize that the current analysis may underestimate the rate ratios for de novo variants in simplex TD families.…”
Section: Discussionmentioning
confidence: 95%
“…Of note, the ascertainment strategies used in both TD cohorts did not restrict to apparently simplex families, as was done in the SSC. Given the evidence for an increased burden of de novo variation in simplex versus multiplex families in ASD (e.g., Leppa et al, 2016), it would be reasonable to hypothesize that the current analysis may underestimate the rate ratios for de novo variants in simplex TD families.…”
Section: Discussionmentioning
confidence: 95%
“…Several of these CNVs were recently reported by Leppa et al in which they analyzed 1532 families to assess the impact of CNVs on the risk of ASD in families with multiple affected individuals. They observed both deletion and duplication of inherited variants spanning WWOX in 9 affected children, with very high odds ratio . Even though some of the duplications shown in Figure of individuals with ASD extend 5′ upstream of WWOX (none >0.5 Mbp), Leppa et al concluded that WWOX is the target of a rare low‐penetrance ASD associated locus .…”
Section: Wwox Is a Hot Spot For Germline Cnv Polymorphismsmentioning
confidence: 99%
“…They observed both deletion and duplication of inherited variants spanning WWOX in 9 affected children, with very high odds ratio . Even though some of the duplications shown in Figure of individuals with ASD extend 5′ upstream of WWOX (none >0.5 Mbp), Leppa et al concluded that WWOX is the target of a rare low‐penetrance ASD associated locus . In another recent report, Mignot et al identified deleterious WWOX deletions in children affected with infantile epileptic encephalopathy (EIEE28, OMIM: 616211) in families where either both parents were carriers of heterozygous WWOX copy number deletions or one parent harbored a heterozygous copy number deletion and the other parent a heterozygous loss of function WWOX point mutation .…”
Section: Wwox Is a Hot Spot For Germline Cnv Polymorphismsmentioning
confidence: 99%
“…In light of these findings, it is hypothesized that detection of both inherited and spontaneous ( de novo ) mutations could be highly productive approaches to gene discovery, similar to the utility of these approaches in prior studies of ASD (Sanders et al, 2015; Leppa et al, 2016) and schizophrenia (Fromer et al, 2014; McCarthy et al, 2014). To date, no gene variants have been reported that increase the risk for stereotypies, yet these studies are underway in our lab and others.…”
Section: Genetic Riskmentioning
confidence: 99%